Effect of Electronic Messaging on Physical Activity Participation among Older Adults. (17th May 2016) - Antoine Parker, Chantrell; Ellis, Rebecca
Abstract : The purpose of this study was to determine if electronic messaging would increase min of aerobic physical activity (PA) among older adults. Participants were active older adults (n = 28 ; M age = 60 years, SD = 5.99, and range = 51–74 years). Using an incomplete within-subjects crossover design, participants were randomly assigned to begin the 4-week study receiving the treatment condition (a morning and evening text message) or the control condition (an evening text message). Participants self-reported min of completed aerobic PA by cell phone text. The 1-way within-subjects ANOVA showed significant group differences (p < 0.05 ). Specifically, when participants were in the treatment condition, they reported significantly greater average weekly min of aerobic PA (M = 96.88 min, SD = 62.9) compared to when they completed the control condition (M = 71.68 min, SD = 40.98). Electronic messaging delivered via cell phones was effective at increasing min of aerobic PA among older adults.